Perlindungan Hukum Pemanggilan dan Pengambilan Minuta Akta Notaris Paska Berlakunya UU No. 2 Tahun 2014 Tentang Perubahan Atas UU No. 30 Tahun 2004 Tentang Jabatan Notaris (UUJN-P) - Prabowo, Muhammad Rikaz (Jurnal Hukum Novelty, 2016)
This paper discusses legal protection for Notaries-Function; in terms of the request upon the copies of the deed minuta, Notarial-deeds protocol, and the calling of Notaries-vocation in legal processes. The identification of the problemis to understand mechanisms of legal protections for Notaries and MKNâs roles and to discussnotariesâ refusal rights and refusal obligation. Based on the literature review and studies on the literatures and legal resources, it can be concluded that: First, the mechanisms of legal protection for request upon the copies of the minuta, the protocol takin of the notary, and the calling of notary for investigation purposes, by investigating-officers, public-prosecutors and judges- require approval of the Regional Supervisory Council as stated in Article 66 paragraph (1) Act Number 30 2004. In 2013 âthe phrase of the MPDâs approvalâ is canceled by Constitutional Court through the decree number 49/PUU/X/2012 for not having legal binding. Second, the MKN is a new agency formed with the establishment of the Act Number 2 2014 concerning the amendment of the Act Number 30 2004 concerning Notariesâ functions (UUJN-P). One of MKN authorities was similar with authorities of the MPD before it was revoked by the MK in 2013. However, the MK had not been established because the Permenkumham on MKS was still being harmonized. Third, the Refusal-Rights are rights for not speaking and giving any statements related to deeds, as a witness in prosecutions and courts. These rights are based on Articles in the Acts, such as the KUHAP, KUH Perdata, HIR and the Act Number 5 1986 concerning state administrative law. The Act Number 30 Year 2004Â  concerning Notaries-functions (UUJN-P) stipulates this provisions as refusal-obligations which mean that it must be executed imperatively, based on the Article 4 paragraphÂ  (2), the Article 16 paragraphÂ  (1) letter f, and the Article 54 clause (1). The violation of these obligations shall be the subject to administrative sanctions ranging from warning up to dishonorable discharge by the UUJN-P. Criminal sanctions rely on general provisions of through KUHAP, especially the Article 322 concerning violations for divulging confidential information giving away in functions.